(untitled) (Journal of Naval Architecture and Marine Engineering, 2014)
The problem of unsteady MHD free convective, incompressible electrically conducting, non-Newtonian fluid through porous medium bounded by an infinite porous plate in the presence of constant suction has been studied. A magnetic field of uniform strength is assumed to be applied normal to the plate. The equations governing the fluid flow which are highly nonlinear are reduced to linear by using perturbation method and have been solved subject to the relevant boundary conditions. It is noted that the velocity of the fluid is increased as Soret number and suction parameter increase, whereas reverse phenomenon is observed in case of magnetic field strength and sink strength. DOI: http://dx.doi.org/10.3329/jname.v11i2.17563